Effects of Methyl Jasmonate on Anthocyanin Accumulation, Ethylene Production, and CO2 Evolution in Uncooled and Cooled Tulip Bulbs - M. Saniewski, M.; Miszczak, A.; Kawa-Miszczak, L.; Wegrzynowicz-Lesiak, L.E.Miyamoto, K.; Ueda, J.
Effects of methyl jasmonate (JA-Me)on anthocyanin accumulation, ethylene production, and CO2 evolution in uncooled and cooled tulips (Tulipa gesneriana L. cvs. Apeldoorn and Gudoshnik)were studied. JA-Me stimulated anthocyanin accumulation in stems and leaves from uncooled and cooled bulbs of both cultivars. The highest level of anthocyanin accumulation was observed in leaves from cooled bulbs treated with 200 7L/liter JA-Me. In sprouting bulbs treated with 100 7L/liter and higher concentrations of JA-Me, the ethylene production began to increase at 3 days after treatment, being extremely greater in uncooled bulbs than in cooled ones. JA-Me also stimulated CO2 evolution in both cultivars, depending on its concentrations. CO2 evolution in sprouting bulbs was not affected by cooling treatment. These results suggest that anthocyanin accumulation by JA-Me in tulip leaves is not related to ethylene production stimulated by JA-Me
Keywords: ANTHOCYANIN; BULBS; CO 2; ETHYLENE; METHYL JASMONATE; TULIP